2012
DOI: 10.1016/j.tourman.2011.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of podcast tours on tourist experiences in a national park

Abstract: This study examines the influence of podcast tours on tourist experiences. Based on theoretical accounts that human voices convey rich social information, this study proposes that podcast tours increase perceived social presence and mindfulness that lead to enhanced tourist experiences and environmental stewardship. A field experiment was conducted at a national park using MP3 players containing podcast tours based on four experimental conditions: 2 information source compositions (single vs. multiple narrator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
158
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(179 citation statements)
references
References 92 publications
13
158
0
8
Order By: Relevance
“…Hedonics incorporates enjoyment, fun, stimulation and other emotional aspects of the experience [88] as opposed to its utilitarian meaning [86]. Escape is defined as an experience through which tourists feel immersed in the environment at the heritage site and, thus, escapes the routine [21,92]. Experiential heritage tourism requires recognition of another component of the experience [86,87], relating to the quality of the service received at the heritage site or attraction [87,88].…”
Section: The Tourism Experience At Heritage Sitesmentioning
confidence: 99%
“…Hedonics incorporates enjoyment, fun, stimulation and other emotional aspects of the experience [88] as opposed to its utilitarian meaning [86]. Escape is defined as an experience through which tourists feel immersed in the environment at the heritage site and, thus, escapes the routine [21,92]. Experiential heritage tourism requires recognition of another component of the experience [86,87], relating to the quality of the service received at the heritage site or attraction [87,88].…”
Section: The Tourism Experience At Heritage Sitesmentioning
confidence: 99%
“…Different from traditional marketing, Word-of-Mouth would change the market point from the relationship between brand and individual customer to the interaction among customers. Moreover, Oral Suggestion did not present commercial motivation that consumers would consider Oral Suggestion with higher reliability than advertisement (Kang and Gretzel 2012). Some researchers discovered that consumers would depend on others' opinions when evaluating a new product or a new service (Kim & Lee, 2011); or, the effects among people would became critical when a product complexity was enhanced and objective and specific evaluation criteria were insufficient (Hsu, 2016).…”
Section: Word-of-mouthmentioning
confidence: 99%
“…For example, podcasts are interpretive media in the form of audio or video files for computers or portable media devices (e.g., cellular phones and tablets) that users consume by streaming online or downloading to their device [113]. Podcasts serve informational functions in that they are used for learning, knowledge acquisition and sharing, and education [102].…”
Section: Using Informational Functionsmentioning
confidence: 99%
“…In one study, podcasts with multiple narrators (as opposed to single narrators) were shown to significantly enhance tourist experiences in a national park, and consequently positive attitudes and intentions toward protecting the park [113]. Perceptions of social presence represented a key mechanism in this process in addition to an enhanced nature experience.…”
Section: Experientialmentioning
confidence: 99%